Tolerable pain reduces gastric fundal accommodation and gastric motility in healthy subjects: a crossover ultrasonographic study. Issue 1 (December 2017) - Hasuo, Hideaki; Kusunoki, Hiroaki; Kanbara, Kenji; Abe, Tetsuya; Yunoki, Naoko; Haruma, Ken; Fukunaga, Mikihiko
Abstract Background Obstacles to pain management include patients' reluctance to inform healthcare provides about their pain, and differences in the pain management aims between patients and healthcare providers. The objective of this study was to evaluate whether tolerable pain influences gastric fundal accommodation and gastric motility in healthy subjects. Methods We undertook a crossover comparison study to evaluate gastric fundal accommodation and gastric motility in 74 healthy subjects in the presence or absence of tolerable pain. The intensity of tolerable pain was defined as the upper limit of pain compatible with comfortable daily life. Pain was generated by clipping a clothes pin to the ear lobe, and the intensity of pain was adjusted by inserting the gauze between the ear lobe and the pin. Gastric fundal accommodation and gastric motility were assessed by external ultrasonography. The cross-sectional area of the proximal stomach was measured after subjects had taken 100 mL-liquid meals four times, then the amplitude and frequency of antral contractions were measured. Results The median numerical rating scale of tolerable pain was 3 (interquartile rang 2–4). Gastric fundal accommodation, gastric motility and gastric emptying were all significantly impaired by tolerable pain (P < 0.001 for all comparisons). Conclusions Even tolerable pain can reduce gastric fundal accommodation and gastric motility, which could result in anorexia or decreased quality of life. Our findings provide important insights into pain management education for patients tolerating pain and healthcare providers encouraging patients to tolerate pain. This study was registered retrospectively.